Multimodality imaging for the quantitative assessment of mitral regurgitation - Chew, Pei G.; Bounford, Katrina; Plein, Sven; Schlosshan, Dominik; Greenwood, John P. (Quantitative Imaging in Medicine and Surgery, 2018)
The natural history of mitral regurgitation (MR) results in significant morbidity and mortality. Innovations in non-invasive imaging have provided new insights into the pathophysiology and quantification of MR, in addition to early detection of left ventricular (LV) dysfunction and prognostic assessment in asymptomatic patients. Transthoracic (TTE) and transesophageal (TOE) echocardiography are the mainstay for diagnosis, assessment and serial surveillance. However, the advance from 2D to 3D imaging leads to improved assessment and characterization of mitral valve (MV) disease. Cardiovascular magnetic resonance (CMR) is increasingly used for MR quantitation and can provide an alternative imaging method if echocardiography is suboptimal or inconclusive. Other techniques such as exercise echocardiography, tissue Doppler imaging and speckle-tracking echocardiography can further offer complementary information on prognosis. This review summarises the current evidence for state-of-the-art cardiovascular imaging for the investigation of MR. Whilst advanced echocardiographic techniques are superior in the evaluation of complex MV anatomy, CMR appears the most accurate technique for the quantification of MR severity. Integration of multimodality imaging for the assessment of MR utilises the advantages of each imaging technique and offers the most comprehensive assessment of MR.